Dysfunctional high-density lipoprotein from HIV+ individuals promotes monocyte-derived foam cell formation in vitro. (13th November 2017) - Angelovich, Thomas A.; Hearps, Anna C.; Oda, Michael N.; Borja, Mark S.; Huynh, Diana; Homann, Stefanie; Jaworowski, Anthony; Kelesidis, Theodoros
Abstract : Objective: The role of high-density lipoprotein (HDL) function in HIV-related atherosclerotic cardiovascular disease (CVD) is unclear. HDLs isolated from HIV + [HIV(+)HDL] and HIV-uninfected individuals [HIV(–)HDL] were assessed for HDL function and ability to promote monocyte-derived foam cell formation (MDFCF; a key event in HIV-related CVD) ex vivo . Design/methods: Using an established in-vitro model of atherogenesis and plasma samples from an established cross-sectional study of virologically suppressed HIV + men on stable effective antiretroviral therapy and with low CVD risk (median age: 42 years; n  = 10), we explored the impact of native HDL [HIV(+)HDL] on MDFCF. In this exploratory study, we selected HIV(+)HDL known to be dysfunctional based on two independent measures of impaired HDL function: antioxidant (high HDLox ) ability of HDL to release apolipoprotein A-I (ApoA-I) (low HDL-ApoA-I exchange). Five healthy men matched by age and race to the HIV + group were included. Given that oxidation of HDL leads to abnormal HDL function, we also compared proatherogenic effects of HIV(+)HDL vs. chemically derived HDLox . The ex-vivo atherogenesis assay was performed using lipoproteins (purchased or isolated from plasma using ultracentrifugation) and monocytes purified via negative selection from healthy donors. Results: HIV(+)HDL known to have reduced antioxidant function and rate of HDL/ApoAI exchange promoted MDFCF to a greater extent than HDL (33.0 vs. 26.2% foam cells; P  = 0.015). HDL oxidized in vitro also enhanced foam cell formation as compared with nonoxidized HDL ( P  < 0.01). Conclusion: Dysfunctional HDL in virologically suppressed HIV + individuals may potentiate atherosclerosis in HIV infection by promoting MDFCF. The role of HDL function in HIV-related atherosclerotic CVD is unclear. HDL isolated from HIV + [HIV(+)HDL] and HIV-uninfected individuals [HIV(−)HDL] were assessed for HDL function and ability to promote foam cell formation ex vivo . HIV(+)HDL known to have reduced antioxidant function and rate of HDL/ApoA1 exchange promoted MDFCF to a greater extent than HDL(−)HDL (33.0 vs. 26.2% foam cells. Subject codes: Inflammation, Lipids and Cholesterol, Vascular Biology, Oxidant Stress, Atherosclerosis Abstract : Supplemental Digital Content is available in the text